Leadership style preferences in Bangladesh’s SMEs: A study on transformational, transactional, and laissez-faire leadership - Manir Hossin; Shah Azam; Shamim Hossain (Business, Management and Economics Engineering, 2024)
Purpose – over the years, small and medium enterprises (SMEs) have grappled with the challenge of adopting appropriate leadership styles domestically and globally. This study, thus, seeks to identify the prevalent leadership styles in Bangladesh’s SME sector, with a specific em- phasis on transformational, transactional, and laissez-faire leadership.